Factors associated with passive immunity transfer in dairy calves: combined effect of delivery time, amount and quality of the first colostrum meal. (17th October 2017) - Lora, I.; Barberio, A.; Contiero, B.; Paparella, P.; Bonfanti, L.; Brscic, M.; Stefani, A. L.; Gottardo, F.
Abstract : Despite the well-known importance of an adequate colostral immunoglobulin (Ig) transfer to calf health and survival, failed transfer of passive immunity (FTPI) remains a widespread problem in dairy farming. The aim of this study was to investigate the management factors associated with FTPI in newborn calves, evaluating particularly the combined effect of delivery time, amount and quality of the first colostrum meal. The study was conducted from March to August 2014 on 21 Italian dairy farms. Farmers were asked as first to answer a farm-level questionnaire on calf management. Blood sampling was then performed on overall 244 calves (1 to 5 days of age) born from Holstein cows, and a sample of the first colostrum meal of each calf was collected. Individual information on calves and the respective colostrum management were recorded. Serum and colostrum Ig concentrations were assessed by electrophoresis. A mixed effects multivariable logistic regression model was used to investigate the association of the variables obtained from both the management questionnaire and the individual calf data with FTPI (calf serum Ig concentration <10.0 g/l). A cumulative colostrum management score (CMS) that considered delivery time, amount and quality of the first colostrum meal was generated for 236 calves, with higher values indicating better colostrum management. Overall, 41.0% of the calves were found having FTPI, and within-farm percentage of FTPI was over 20.0% in 71.4% of the farms. The risk of having FTPI was higher both for Holstein purebred calves compared with Holstein-beef crossbreds and for females compared with males. Moreover, it increased by 13% with every hour of delay of the first colostrum meal provision since birth, whereas it decreased by 59% and 3%, respectively, with every additional liter of colostrum given and every additional gram of Ig per liter contained in the colostrum fed. Calf serum Ig concentration varied significantly according to the CMS, increasing by 1.53 g/l with every additional CMS point. In order to completely avoid FTPI, calves should receive at least 2.5 l of high-quality colostrum (Ig concentration >87.6 g/l) within 1.0 h from birth. Considerable improvements are still needed about colostrum management for newborn calves in dairy farms. The results of this study will help in developing farm-specific programs for reducing the occurrence of FTPI.